HIV infection among refugees, asylum seekers and unaccompanied foreign minors attending an outpatient clinic in Reggio Emilia (Northern Italy) in 2022–2023 - Corsaro, Alice; Bonvicini, Francesca; Federica, Violi; Sparano, Marina; Castagni, Ilaria; Casoni, Carmen; Mazzini, Anna; Filippini, Tommaso; Vinceti, Marco (Discover public health, 2025)
Introduction In Europe, migrant populations demonstrated a high risk of infection disease, possibly due to both pre-migratory and post-migratory factors. In particular, investigating HIV infection prevalence is a public health priority. In this study, we aimed to assess the prevalence of HIV infection in refugees, asylum seekers and unaccompanied foreign minors (UFM) accessing a targeted outpatient clinic in the province of Reggio Emilia, Northern Italy. Methods We analyzed data from the serological screening for HIV carried out among refugees, asylum seekers and UFM by a dedicated “Centre for Health of Foreign Family”, at the time of the first medical examination in the 2022–2023 period. Results Of 1351 subjects (mean age 25.3 ± 7.9), 85.2% were males and 19.5% were under 18 years. The majority (74.6%) were from Africa (51.4% and 23.2% from the sub-Saharan area and North Africa, respectively), and 20.5% from Asia (11.8% from Bangladesh, 7.7% from Pakistan and 1% from Afghanistan, respectively). We found 10 (0.74%) HIV-positive people, with a prevalence increasing from 0.26% (1/389) in 2022 to 0.94% (9/962) in 2023 with a relative risk of infection of 3.6 (95% CI 0.5–28.7). All positive cases were from sub-Saharan Africa (60% from Ivory Coast), and 80% were females aged between 23 and 44 years. Conclusions Our findings suggest a possible increased risk of HIV infection among refugees and asylum seekers in 2023 compared to 2022, especially in females and in relation to the sub-Saharan area.